Carbon material and preparation method and application method thereof

By using polyhydroxyphenol crosslinking agents and biomass to crosslink condensation reaction with aromatic-rich oil during the preparation of carbon materials, and carbide treatment, the problem of insufficient metal ion storage capacity of condensed polycyclic polynuclear aromatic resin-based carbon materials is solved, and higher electrochemical performance is achieved.

CN119873795AActive Publication Date: 2025-04-25EAST CHINA UNIV OF SCI & TECH

Patent Information

Application Number
CN202510120911.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-24
Publication Date
2025-04-25
Estimated Expiration
2045-01-24

AI Technical Summary

Technical Problem

The prior art is difficult to improve the metal ion storage capacity of condensed polycyclic polynuclear aromatic resin-based carbon materials, especially when used in the negative electrode of alkali metal ion batteries with larger ion radius.

Method used

Polyhydroxyphenol crosslinking agent is obtained by mixing paraformaldehyde, phenolic substances and alkaline solution, and then aromatic-rich hydrocarbon oil and biomass are mixed with crosslinking and condensation reaction to obtain a condensed polycyclic polynuclear aromatic resin, and carbon material is prepared by carbonization treatment. This method regulates the structural performance of the resin by introducing biomass and polyhydroxyphenol crosslinking agents and improves the metal ion storage capacity of carbon materials.

Benefits of technology

The metal ion storage capacity of condensed polycyclic polynuclear aromatic resin-based carbon materials is significantly improved, making it more suitable for alkali metal ion batteries with larger ion radius, and improving the overall electrochemical performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119873795A_ABST
    Figure CN119873795A_ABST
Patent Text Reader

Abstract

The invention relates to a carbon material as well as a preparation method and an application method thereof, and the preparation method comprises the following steps: mixing paraformaldehyde, a phenolic substance and an alkaline solution, and reacting to obtain a polyhydroxy phenolic cross-linking agent; the method comprises the following steps: mixing aromatic hydrocarbon-rich oil with biomass, adding a polyhydroxy phenol crosslinking agent, and carrying out a crosslinking condensation reaction to obtain condensed polycyclic polynuclear aromatic hydrocarbon resin; according to the method, the condensed polycyclic polynuclear aromatic resin is carbonized to obtain the carbon material, so that the method for preparing the high-performance carbon material capable of being used as the sodium-ion battery electrode material by taking petrochemical aromatic hydrocarbon-rich oil and biomass as raw materials is provided, and an oxygen-containing functional group can be introduced into the obtained condensed polycyclic polynuclear aromatic resin to prepare the high-performance carbon material capable of being used as the sodium-ion battery electrode material. Therefore, the metal ion storage capacity of the finally prepared condensed polycyclic polynuclear aromatic resin-based carbon material can be greatly improved, and the condensed polycyclic polynuclear aromatic resin-based carbon material can be well applied to metal ion batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of carbon materials, and in particular to a carbon material and a preparation method and an application method thereof. Background Art

[0002] With the development of the petrochemical industry, the position of ethylene cracking process and catalytic cracking process in the petrochemical industry is becoming more and more important. These two types of processes will produce two kinds of aromatic oils, ethylene tar (accounting for about 15% of ethylene production capacity) and catalytic cracking diesel (accounting for about 30% of diesel production capacity) during operation. Among them, ethylene tar is mainly used as fuel in industry, which not only causes environmental problems such as greenhouse effect and air pollution, but also causes waste of its rich aromatic resources. Catalytic diesel is mainly converted into light aromatics and benzene-toluene-xylene mixture through hydrogenation process to achieve the upgraded utilization of catalytic diesel, but these processes are energy-intensive and have low economic benefits. Therefore, how to efficiently and reasonably convert ethylene tar and catalytic diesel into high value-added materials is of great significance and practical value. Since both byproduct oils are rich in aromatics, they are rich in carbon and prone to electrophilic substitution reactions. Therefore, using these two characteristics to transform the two rich aromatics oils into carbon-rich macromolecular polymers (condensed polycyclic polynuclear aromatic resins) and then carbonize them to obtain high-value-added carbon materials for electrodes is an effective way to efficiently utilize the two rich aromatics oils. This can not only effectively transform the aromatics in the byproduct oils into high-value-added carbon materials, but also improve the economic benefits of the oil refining system and improve the oil processing process.

[0003] Generally, when carbon materials are used as negative electrodes for batteries with alkali metal ions (e.g., sodium ions) with slightly larger ionic radius, there are certain requirements for the interlayer spacing and disorder of the carbon materials. However, both ethylene tar and catalytic diesel are rich aromatic oils. Although they can be converted into condensed polycyclic polynuclear aromatic resin-based carbon materials using traditional crosslinking agents (e.g., terephthalate, divinylbenzene, trioxymethylene, benzaldehyde, and terephthalaldehyde), they exhibit soft carbon behavior similar to that of asphalt, i.e., low interlayer spacing and disorder, which is not conducive to the storage of alkali metal ions with large ionic radius.

[0004] Therefore, how to improve the metal ion storage capacity of condensed polycyclic polynuclear aromatic resin-based carbon materials has become an urgent problem to be solved. Summary of the invention

[0005] The purpose of the present application is to provide a carbon material and a preparation method and an application method thereof, so as to enhance the metal ion storage capacity of a condensed polycyclic polynuclear aromatic hydrocarbon resin-based carbon material.

[0006] An embodiment of the present application provides a method for preparing a carbon material, which comprises: mixing polyformaldehyde, a phenolic substance and an alkaline solution and reacting the mixture to obtain a polyhydroxyphenol cross-linking agent; mixing aromatic-rich oil with biomass and adding the polyhydroxyphenol cross-linking agent to carry out a cross-linking condensation reaction to obtain a condensed polycyclic polynuclear aromatic resin; and carbonizing the condensed polycyclic polynuclear aromatic resin to obtain a carbon material.

[0007] The method comprises: mixing polyformaldehyde, phenolic substances and alkaline solution and reacting them to obtain a polyhydroxyphenol crosslinking agent, comprising: dissolving polyformaldehyde and phenolic substances in an alkaline solution to form a mixed solution; stirring the mixed solution at a first predetermined temperature for a first predetermined time, and then standing and separating the mixed solution for a second predetermined time to obtain the polyhydroxyphenol crosslinking agent, wherein the first predetermined temperature is 20 to 90° C., the first predetermined time is 3 to 48 hours, and the second predetermined time is 6 to 24 hours.

[0008] The phenolic substances include one or more of phenol, catechol, hydroquinone, resorcinol, phloroglucinol, p-tert-butylphenol, p-tert-octylphenol, and p-methylphenol; the alkaline solution is an aqueous solution of any one or more combinations of sodium hydroxide, potassium hydroxide, and ammonia water, and the mass concentration of the alkaline solution is 2% to 50%; the mass ratio of polyformaldehyde to the phenolic substances is (30 to 55): (45 to 70); the mass ratio of polyformaldehyde to the alkali in the alkaline solution is (1 to 2.5): (0.5 to 1.5).

[0009] The aromatics-rich oil includes one or more of catalytic diesel, ethylene tar, ethylene tar residue and ethylene tar light fraction; the biomass includes one or more of hydrolyzed tannic acid, condensed tannic acid, cellulose, starch and lignin.

[0010] The mass ratio of the aromatic-rich oil, the biomass and the polyhydroxyphenol cross-linking agent is (45-55): (5-20): (25-50).

[0011] The method comprises: mixing the aromatic-rich oil with the biomass, adding a polyhydroxyphenol cross-linking agent, performing a cross-linking condensation reaction, and obtaining a condensed polycyclic polynuclear aromatic resin, comprising: mixing the aromatic-rich oil with the biomass, adding a polyhydroxyphenol cross-linking agent, performing stirring reaction at a second predetermined temperature for a third predetermined time, and obtaining a condensed polycyclic polynuclear aromatic resin, wherein the second predetermined temperature is 120 to 260°C, and the third predetermined time is 2 to 10 hours.

[0012] The step of carbonizing the condensed polycyclic polynuclear aromatic hydrocarbon resin to obtain the carbon material comprises: calcining the condensed polycyclic polynuclear aromatic hydrocarbon resin to obtain the carbon material.

[0013] The calcination temperature rise rate is 1-5°C / min; the calcination end temperature is 800-1600°C; the calcination heat preservation time is 1-10h; and the calcination is carried out under a protective gas atmosphere.

[0014] The embodiment of the present application also provides a carbon material, which is prepared by any of the above-mentioned methods for preparing carbon materials.

[0015] The embodiment of the present application also provides an application method of the carbon material, and the application method of the carbon material comprises: using the above-mentioned carbon material to make a negative electrode of a metal ion battery.

[0016] The carbon material and its preparation method and application method provided by the present application are as follows: polyformaldehyde, phenolic substances and alkaline solution are mixed and reacted to obtain a polyhydroxyphenol crosslinking agent, and then aromatic-rich oil is mixed with biomass and the polyhydroxyphenol crosslinking agent is added to carry out a crosslinking condensation reaction to obtain a condensed polycyclic polynuclear aromatic resin, and then the condensed polycyclic polynuclear aromatic resin is carbonized to obtain a carbon material, thereby providing a method for preparing a high-performance carbon material that can be used as an electrode material for a sodium ion battery using petrochemical aromatic-rich oil and biomass as raw materials, and the method is rich in polar functional groups. The biomass is introduced into the petrochemical rich aromatic oil, and the petrochemical rich aromatic oil and the biomass rich in polar functional groups are interconnected through a polyhydroxyphenol cross-linking agent, so that polar functional groups (for example, oxygen-containing functional groups) can be introduced into the obtained condensed polycyclic polynuclear aromatic resin to regulate the structural properties of the final condensed polycyclic polynuclear aromatic resin-based carbon material, thereby greatly improving the metal ion storage capacity of the final condensed polycyclic polynuclear aromatic resin-based carbon material, making it conducive to the storage of alkali metal ions with large ion radius, and can be well applied in metal ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] The technical solution and other beneficial effects of the present application will be made apparent by describing in detail the specific implementation methods of the present application in conjunction with the accompanying drawings.

[0018] Figure 1 It is a schematic diagram of the process of preparing the carbon material provided in the embodiment of the present application. DETAILED DESCRIPTION

[0019] The present application is further described in detail below in conjunction with the accompanying drawings and examples. It is particularly noted that the following examples are only used to illustrate the present application, but are not intended to limit the scope of the present application. Similarly, the following examples are only some embodiments of the present application rather than all embodiments, and all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of this application.

[0020] In the following description of the present application, reference is made to “some embodiments”, which describe a subset of all possible embodiments, but it can be understood that “some embodiments” may be the same subset or different subsets of all possible embodiments and may be combined with each other without conflict.

[0021] In the following description of the present application, the terms "first\second\third" involved are merely used to distinguish similar objects and do not represent a specific ordering of the objects. It can be understood that "first\second\third" can be interchanged with a specific order or sequence where permitted, so that the embodiments of the present application described here can be implemented in an order other than that illustrated or described here.

[0022] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. If there is any conflict, this specification takes precedence. The terms used herein are only for the purpose of describing the embodiments of this application and are not intended to limit this application.

[0023] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.

[0024] The following is a detailed description with reference to specific embodiments. It should be noted that the serial numbers of the following embodiments are not intended to limit the preferred order of the embodiments.

[0025] See also Figure 1 , Figure 1 : is a schematic diagram of a process for preparing a carbon material provided in an embodiment of the present application. The specific process of the method for preparing the carbon material may be as follows:

[0026] Step S11: mixing paraformaldehyde, phenolic substances and alkaline solution and reacting them to obtain a polyhydroxyphenol cross-linking agent.

[0027] In this embodiment, hydroxymethyl groups are attached to phenolic substances through polyformaldehyde, so that the phenolic substance molecules have multiple cross-linkable active groups, that is, a polyhydroxyphenol cross-linking agent is obtained, and the obtained polyhydroxyphenol cross-linking agent can be specifically a polyol, so that it can act on aromatic oil molecules such as ethylene tar and catalytic diesel to synthesize condensed polycyclic polynuclear aromatic resins with a high content of oxygen-containing functional groups.

[0028] Among them, the phenolic substances may include one or more of phenol, catechol, hydroquinone, resorcinol, phloroglucinol, p-tert-butylphenol, p-tert-octylphenol, and p-methylphenol, for example, specifically phenol, catechol, phloroglucinol, or p-tert-octylphenol.

[0029] The alkaline solution can be an aqueous solution of any one or more combinations of sodium hydroxide, potassium hydroxide and ammonia water, for example, it can be an ammonia solution, a sodium hydroxide solution or a potassium hydroxide solution. In addition, the mass concentration of the alkaline solution can be 2% to 50%, for example, it can be 2%, 5%, 12%, 20%, 30% or 40%, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable. In some examples, the alkaline solution can be a sodium hydroxide solution with a mass concentration of 2%, or a potassium hydroxide solution with a mass concentration of 10%, or a sodium hydroxide solution with a mass concentration of 15%, or a potassium hydroxide solution with a mass concentration of 20%, or a ammonia solution with a mass concentration of 30%.

[0030] Furthermore, it should be noted that in the embodiments of the present application, by using polyformaldehyde to convert phenolic substances into polyhydroxyphenol cross-linking agents under alkaline conditions, on the one hand, the polyhydroxyphenol cross-linking agents can contain more oxygen-containing functional groups than traditional cross-linking agents (for example, terephthalic acid methanol, divinylbenzene, trioxymethylene, benzaldehyde and terephthalaldehyde), and on the other hand, the polyhydroxyphenol cross-linking agents are rich in oxygen-containing functional groups, which makes them beneficial to promote deep cross-linking between macromolecular resins in the subsequent process of carbonizing the obtained condensed polycyclic polynuclear aromatic resin to obtain carbon materials.

[0031] In some embodiments, in the above step S11, the mass ratio of the paraformaldehyde and the phenolic substance used can be (30-55): (45-70), for example, specifically 30:70, 38:62, 43:57, 55:45 or 47:53, but it is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable. In this way, by controlling the mass ratio of the paraformaldehyde and the phenolic substance used in the above step S11 within a specific range, it is possible to ensure that a polyhydroxy structure is formed between the paraformaldehyde and the phenolic substance, thereby effectively improving the cross-linking effect of the cross-linking agent (i.e., the polyhydroxyphenol cross-linking agent) obtained in the above step S11. In addition, the amount of paraformaldehyde used in the above step S11 can be controlled to prevent the cross-linking agents obtained in the above step S11 from undergoing excessive condensation reactions to form polycondensates, thereby ensuring the cross-linking effect of the cross-linking agent obtained in the above step S11.

[0032] In some embodiments, in the above step S11, the mass ratio of the polyformaldehyde used and the alkali in the alkaline solution used can be (1-2.5): (0.5-1.5), for example, it can be 0.8:1, 2:1, 3.2:1 or 4.0:1, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0033] In some embodiments, the above step S11 may specifically include:

[0034] Step S111. dissolving paraformaldehyde and phenolic substances in an alkaline solution to form a mixed solution;

[0035] Step S112: stirring the mixed solution at a first predetermined temperature for a first predetermined time, and then standing and separating for a second predetermined time to obtain a polyhydroxyphenol cross-linking agent.

[0036] Specifically, after dissolving polyformaldehyde and phenolic substances in an alkaline solution to form a mixed solution, the formed mixed solution can be stirred for reaction at a first predetermined temperature for a first predetermined time, and then allowed to stand for separation for a second predetermined time to obtain a polyhydroxyphenol crosslinking agent.

[0037] Wherein, the first predetermined temperature can be 20~90 ℃, for example, specifically can be 25 ℃ or 60 ℃, but is not limited to the numerical value listed, and other numerical values ​​not listed in the numerical range are also applicable. The first predetermined time can be 3~48h, for example, specifically can be 2h, 5h, 15h, 20h, 24h, 35h or 48h, but is not limited to the numerical value listed, and other numerical values ​​not listed in the numerical range are also applicable. In this way, by controlling the time and temperature of the stirring reaction within a specific range, on the one hand, sufficient time can be provided to ensure that the phenolic substance is completely converted into a polyhydroxyphenol cross-linking agent, and on the other hand, the reaction raw materials can be fully mixed.

[0038] The second predetermined time may be 6 to 24 hours, for example, 6 hours, 12 hours, 24 hours or 8 hours, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable. Thus, by controlling the static separation time within a specific range, on the one hand, the metal salt (for example, sodium salt) in the reaction system can be completely protonated, and on the other hand, the cross-linking agent can be completely extracted.

[0039] Furthermore, in a specific implementation, polyformaldehyde and phenolic substances can be mixed in a certain mass ratio, and then an alkaline solution can be added in a certain mass ratio of the alkaline solution to the polyformaldehyde, followed by stirring and reacting at a set temperature for a certain time, and the obtained product can be purified and separated to obtain a polyhydroxyphenol crosslinking agent.

[0040] Step S12: After the aromatic-rich oil and biomass are mixed, a polyhydroxyphenol cross-linking agent is added to carry out a cross-linking condensation reaction to obtain a condensed polycyclic polynuclear aromatic resin.

[0041] The aromatics-rich oil may include at least one of petrochemical aromatics-rich oils such as catalytic diesel, ethylene tar, ethylene tar residue (e.g., ethylene tar coated asphalt residue) and ethylene tar light fraction. The biomass may include at least one of biomasses rich in polar functional groups (e.g., hydroxyl, ether, ester, carboxyl, etc.) such as hydrolyzed tannic acid, condensed tannic acid, cellulose, starch and lignin.

[0042] In this embodiment, by using low-cost petrochemical rich aromatic oil and biomass as raw materials, the polyhydroxyphenol cross-linking agent obtained after the completion of the above step S11 is used to convert the raw materials into condensed polycyclic polynuclear aromatic resins. On the one hand, the raw materials are low-cost, and on the other hand, more oxygen-containing functional groups are introduced into the condensed polycyclic polynuclear aromatic resins through biomass, which can realize the regulation of the content of oxygen-containing functional groups in the condensed polycyclic polynuclear aromatic resins, thereby effectively improving the electrochemical properties of the finally obtained condensed polycyclic polynuclear aromatic resin-based carbon material.

[0043] In some embodiments, in the above step S12, the mass ratio of the aromatic-rich oil, biomass and polyhydroxyphenol cross-linking agent used can be (45-55): (5-20): (25-50), for example, it can be 45:5:50, 45:10:45, 50:5:45 or 55:15:30, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable. In this way, by controlling the usage ratio of the aromatic-rich oil, biomass and cross-linking agent in the above step S12 within a specific range, it is possible to control the amount of oxygen-containing functional groups introduced into the obtained condensed polycyclic polynuclear aromatic resin, thereby achieving controllable preparation of condensed polycyclic polynuclear aromatic resins with different oxygen-containing functional group contents, thereby achieving structural regulation of condensed polycyclic polynuclear aromatic resin-based carbon materials.

[0044] In some embodiments, in the above step S12, the time of the cross-linking condensation reaction can be 2 to 10 hours, for example, 1 to 2 hours. For example, in the above step S12, the time of the cross-linking condensation reaction can be 2 hours, 2.5 hours, 3 hours, 5 hours, 7.5 hours or 10 hours, but is not limited to the listed values, and other values ​​not listed in the numerical range are also applicable.

[0045] In some embodiments, in the above step S12, the temperature of the cross-linking condensation reaction can be 120 to 260° C., for example, can be specifically 170 to 240° C. For example, in the above step S12, the temperature of the cross-linking condensation reaction can be specifically 120° C., 135° C., 145° C., 170° C., 200° C., 220° C., 245° C. or 260° C., but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0046] In some specific embodiments, the above step S12 may specifically include: mixing the aromatic-rich oil with the biomass, adding a polyhydroxyphenol cross-linking agent, stirring and reacting at a second predetermined temperature for a third predetermined time to obtain a condensed polycyclic polynuclear aromatic resin, wherein the second predetermined temperature is 120 to 260° C., and the third predetermined time is 2 to 10 hours.

[0047] Specifically, the aromatic-rich oil and biomass can be mixed in a certain mass ratio, and then a cross-linking agent (i.e., the polyhydroxyphenol cross-linking agent obtained after the completion of the above step S12) and a catalyst (e.g., p-toluenesulfonic acid) can be added to carry out a cross-linking condensation reaction to prepare a condensed polycyclic polynuclear aromatic resin. During the cross-linking condensation reaction, the cross-linking agent connects the aromatic-rich oil and the biomass to each other, thereby introducing polar functional groups into the condensed polycyclic polynuclear aromatic resin through the polar functional groups on the molecular structure of the biomass and the cross-linking agent, so that it can be deeply cross-linked during the subsequent resin carbonization process to regulate the material structural properties such as the interlayer spacing, disorder and specific surface area of ​​the carbon material.

[0048] Furthermore, in a specific implementation, after the cross-linking condensation reaction is completed, the obtained product can be subjected to steps such as dissolution, precipitation, and drying to remove impurities remaining on the resin, thereby obtaining the final product (ie, condensed polycyclic polynuclear aromatic resin).

[0049] Step S13: carbonizing the condensed polycyclic polynuclear aromatic resin to obtain a carbon material.

[0050] In this embodiment, the carbon material obtained after the completion of the above step S13 is a condensed polycyclic polynuclear aromatic resin-based carbon material, which can be used as a sodium ion battery electrode material. Moreover, compared with the existing resin-based carbon material, the carbon material obtained after the completion of the above step S13 can have a larger interlayer spacing and disorder, so that when it is used as a negative electrode material for a sodium ion battery, it can effectively improve the overall electrochemical performance of the sodium ion battery, for example, the reversible capacity of the sodium ion battery at a current density of 100mA / g can reach 260mAh / g.

[0051] It can be understood that, on the one hand, the presence of oxygen-containing functional groups in the condensed polycyclic polynuclear aromatic resin obtained after the completion of the above step S12 is conducive to the formation of a carbon material with a larger interlayer spacing and disorder in the above step S13; on the other hand, the resin-based carbon material prepared by cross-linking and condensing biomass and rich aromatic oil as raw materials with a polyhydroxyphenol cross-linking agent effectively improves the overall electrochemical performance of the sodium ion battery when it is used as a negative electrode material for a sodium ion battery.

[0052] In some embodiments, the condensed polycyclic polynuclear aromatic hydrocarbon resin can be subjected to high temperature carbonization to obtain a carbon material. Specifically, after obtaining the condensed polycyclic polynuclear aromatic hydrocarbon resin, the condensed polycyclic polynuclear aromatic hydrocarbon resin can be calcined to obtain a carbon material.

[0053] The heating rate of the calcination may be 1 to 5°C / min, for example, 2 to 5°C / min. For example, the heating rate of the calcination may be 1°C / min, 1.5°C / min, 2.5°C / min, 4°C / min or 5°C / min, but is not limited to the values ​​listed, and other values ​​not listed within the numerical range are also applicable.

[0054] The end point temperature of the calcination may be 800 to 1600°C, for example, 1000 to 1500°C. For example, the end point temperature of the calcination may be 800°C, 900°C, 1000°C, 1100°C, 1200°C, 1300°C, 1400°C or 1600°C, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable. In this way, by controlling the calcination temperature within a specific range, the condensed polycyclic polynuclear aromatic resin can be completely converted into a carbon material.

[0055] The calcination holding time may be 1 to 10 hours, for example, 2 to 6 hours. For example, the calcination holding time may be 1 hour, 1.5 hours, 3 hours, 5 hours, 7 hours, 8 hours or 10 hours, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0056] The calcination may be performed under a protective gas atmosphere, wherein the protective gas may specifically be argon or nitrogen.

[0057] In some specific embodiments, the condensed polycyclic polynuclear aromatic hydrocarbon resin obtained after the completion of the above step S12 can be heated to a specific temperature at a certain heating rate for carbonization treatment to obtain a condensed polycyclic polynuclear aromatic hydrocarbon resin-based carbon material, and the electrochemical performance of the obtained condensed polycyclic polynuclear aromatic hydrocarbon resin-based carbon material is significantly improved due to the introduction of oxygen-containing functional groups.

[0058] Moreover, in a specific implementation, the condensed polycyclic polynuclear aromatic resin obtained after the completion of the above step S21 can be heated to 800-1600°C at a rate of 1-5°C / min and kept warm for 1-10 hours under an argon atmosphere for calcination to obtain a high-performance carbon material that can be used as an electrode material for a sodium ion battery.

[0059] It should be noted that in the existing technologies for preparing carbon materials using petrochemical aromatic-rich oil:

[0060] Chinese patent document (CN119050351A) discloses that low softening point asphalt is converted into high softening point asphalt by cross-linking agents such as terephthalic alcohol, terephthalaldehyde, benzaldehyde, trioxymethylene, and p-methylbenzaldehyde, followed by plasma oxidation to obtain pre-oxidized asphalt balls, and finally carbonization to obtain asphalt-based hard carbon material. The asphalt-based hard carbon material can be used as a negative electrode material for lithium-ion / sodium-ion batteries, and when the asphalt-based hard carbon material is used as a negative electrode material for sodium-ion batteries, the reversible capacity of the sodium-ion battery can reach 310mAh / g.

[0061] Chinese patent document (CN118479452A) discloses that coal tar pitch, petroleum asphalt and shale asphalt are used as raw materials, dimethoxymethane and p-phenylenedimethyl dimethyl ether are used as cross-linking agents, and asphalt-based super-cross-linked polymers are prepared under the action of concentrated sulfuric acid and dichloromethane, and then carbonization is performed to obtain hard carbon materials for sodium ion battery negative electrodes. The patent provides a simple and efficient preparation method for asphalt-derived hard carbon materials for sodium ion batteries.

[0062] Chinese patent document (CN118419903A) discloses using coal / biomass / asphalt as raw materials, preparing coal and biomass into a uniform mixture by ball milling, and then subjecting the mixture to hydrothermal reaction with asphalt after agglomeration and pre-carbonization treatment, and finally subjecting the mixture to carbonization treatment to obtain a hard carbon material for sodium ion negative electrode having abundant microporous sodium storage sites, providing a simple and easy large-scale production method for the preparation of high-capacity sodium ion negative electrode materials.

[0063] Chinese patent document (CN118324117A) discloses that petroleum asphalt and sucrose are subjected to hydrothermal reaction and then dried to obtain a carbon material for a sodium ion negative electrode.

[0064] Chinese patent document (CN117902565A) discloses cross-linking of asphalt and resin (including phenolic resin, epoxy resin, furan resin, benzoxazine resin) under the action of a cross-linking agent (anhydride substance) to achieve effective molecular structure of the carbon precursor, thereby regulating the disorder, interlayer spacing and pore structure of the carbonization product.

[0065] Chinese patent document (CN116395667B) discloses that asphalt is used as raw material, and pre-treated in a ball mill in different atmospheres such as oxygen, nitrogen, ammonia, phosphine, boron trichloride, hydrogen sulfide, etc. to obtain doped asphalt powder, and then high-temperature carbonization is performed to obtain hard carbon material. The patent provides a method for regulating the doping elements and doping amounts in asphalt by adjusting plasma ball milling parameters to regulate the structural properties of asphalt.

[0066] The above patent documents propose a method for preparing a carbon material for a negative electrode of a sodium ion battery using petrochemical rich aromatics, which includes using a traditional cross-linking agent to increase the softening point of asphalt, pre-oxidation treatment to dope heteroatoms (O, N, P, etc.) in the asphalt structure, hyper-cross-linking to make the asphalt cross-linked with each other, and combining biomass and hydrothermal treatment methods to improve the pore structure and sodium storage sites of the final asphalt-based carbon material. Although these methods provide cheap asphalt and a method for improving its performance for the preparation of carbon materials for negative electrodes of sodium ion batteries, none of them involve a method for preparing a carbon material for a negative electrode of a sodium ion battery using cheap and large amounts of petrochemical rich aromatics oil (ethylene tar and catalytic diesel) combined with biomass, cross-linking and condensing to obtain a condensed polycyclic polynuclear aromatic resin under the action of a phenolic cross-linking agent, and then carbonizing it to obtain a carbon material for a negative electrode of a sodium ion battery.

[0067] Therefore, in view of the current situation that the production capacity of rich aromatic oil products continues to grow but is difficult to utilize, as well as the shortcomings of poor electrochemical performance of carbon materials prepared from traditional petroleum-based resins, the embodiments of the present application provide a method for preparing high-performance carbon materials that can be used as electrode materials for sodium ion batteries using petrochemical rich aromatic oil and biomass as raw materials. In addition, compared with the existing related technologies for preparing carbon materials using petrochemical rich aromatic oil, the method provided in the embodiments of the present application for preparing high-performance carbon materials that can be used as electrode materials for sodium ion batteries using petrochemical rich aromatic oil and biomass as raw materials can, on the one hand, efficiently and environmentally friendly convert rich aromatic oil products and biomass raw materials into high value-added products (i.e., high-performance carbon materials), and on the other hand, can introduce oxygen-containing functional groups into traditional petroleum-based resins, and can achieve the regulation of the content of oxygen-containing functional groups, thereby effectively improving the electrochemical properties of carbon materials such as ion storage capacity, conductivity and performance stability.

[0068] Furthermore, for ease of understanding, the present application is further described in detail below through seven specific embodiments (i.e., Embodiment 1, Embodiment 2, Embodiment 3, Embodiment 4, Embodiment 5, Embodiment 6 and Embodiment 7), and Comparative Examples 1 and 2 are used as controls.

[0069] Example 1

[0070] In Example 1, the specific process of the preparation method of the carbon material can be as follows:

[0071] Step S21. Weigh 10 g of paraformaldehyde and 24 g of phenol, dissolve them in a sodium hydroxide solution with a mass concentration of 2%, and the mass ratio of paraformaldehyde to the alkali (i.e., sodium hydroxide) in the alkaline solution (i.e., sodium hydroxide solution with a mass concentration of 2%) is 0.8. After the paraformaldehyde and phenol are completely dissolved, stir and react at 20° C. for 24 hours, and then stand and separate for 12 hours to obtain a polyhydroxyphenol cross-linking agent;

[0072] Step S22. Weigh 10 g of catalytic diesel, 4.44 g of hydrolyzed tannic acid and 4.81 g of the polyhydroxyphenol crosslinking agent obtained in step S21 above, and stir and react at 160 ° C for 8 h to obtain a condensed polycyclic polynuclear aromatic resin;

[0073] Step S23. Weigh 2 g of the condensed polycyclic polynuclear aromatic resin obtained in the above step S22, heat it to 1200°C at a rate of 1°C / min under an argon atmosphere and keep it warm for 2 hours to obtain a high-performance carbon material that can be used as an electrode material for a sodium ion battery. The carbon material is cooled and dried for later use.

[0074] Example 2

[0075] In Example 2, the specific process of the preparation method of the carbon material can be as follows:

[0076] Step S31. Weigh 10 g of paraformaldehyde and 17.24 g of catechol, dissolve them in a potassium hydroxide solution with a mass concentration of 10%, and the mass ratio of paraformaldehyde to the alkali (i.e., potassium hydroxide) in the alkaline solution (i.e., potassium hydroxide solution with a mass concentration of 10%) is 2. After the paraformaldehyde and catechol are completely dissolved, stir and react at 35° C. for 30 hours, and then stand and separate for 8 hours to obtain a polyhydroxyphenol cross-linking agent;

[0077] Step S32. Weigh 10 g of the remaining ethylene tar coated asphalt, 2.86 g of condensed tannin and 5.14 g of the polyhydroxyphenol crosslinking agent obtained in the above step S31, and stir and react at 180 ° C for 5 h to obtain a condensed polycyclic polynuclear aromatic resin;

[0078] Step S33. Weigh 2 g of the condensed polycyclic polynuclear aromatic resin obtained in the above step S32, heat it to 1000°C at a rate of 2°C / min under an argon atmosphere and keep it warm for 3 hours to calcine it to obtain a high-performance carbon material that can be used as an electrode material for a sodium ion battery. The carbon material is cooled and dried for later use.

[0079] Example 3

[0080] In Example 3, the specific process of the preparation method of the carbon material can be as follows:

[0081] Step S41. Weigh 10 g of paraformaldehyde and 14.29 g of phloroglucinol, dissolve them in a sodium hydroxide solution with a mass concentration of 15%, and the mass ratio of paraformaldehyde to the alkali (i.e., sodium hydroxide) in the alkaline solution (i.e., the sodium hydroxide solution with a mass concentration of 15%) is 3.2. After the paraformaldehyde and phloroglucinol are completely dissolved, stir and react at 45° C. for 15 h, and then stand and separate for 10 h to obtain a polyhydroxyphenol cross-linking agent;

[0082] Step S42. Weigh 10 g of ethylene tar light fraction oil, 1.67 g of lignin and 5.83 g of the polyhydroxyphenol crosslinking agent obtained in the above step S41, and stir and react at 200° C. for 10 h to obtain a condensed polycyclic polynuclear aromatic resin;

[0083] Step S43. Weigh 2 g of the condensed polycyclic polynuclear aromatic resin obtained in the above step S42, heat it to 1400°C at a rate of 5°C / min under an argon atmosphere and keep it warm for 3 hours to calcine it to obtain a high-performance carbon material that can be used as an electrode material for a sodium ion battery. The carbon material is cooled and dried for later use.

[0084] Example 4

[0085] In Example 4, the specific process of the preparation method of the carbon material can be as follows:

[0086] Step S51. Weigh 10 g of paraformaldehyde and 11.11 g of tert-octylphenol, dissolve them in a potassium hydroxide solution with a mass concentration of 20%, and the mass ratio of paraformaldehyde to the alkali (i.e., potassium hydroxide) in the alkaline solution (i.e., a potassium hydroxide solution with a mass concentration of 20%) is 4.0. After the paraformaldehyde and tert-octylphenol are completely dissolved, stir and react at 60° C. for 6 hours, and then stand and separate for 24 hours to obtain a polyhydroxyphenol cross-linking agent;

[0087] Step S52. Weigh 10 g of ethylene tar, 1.25 g of lignin and 7.50 g of the polyhydroxyphenol crosslinking agent obtained in the above step S52, and stir and react at 230° C. for 3 h to obtain a condensed polycyclic polynuclear aromatic resin;

[0088] Step S53. Weigh 2 g of the condensed polycyclic polynuclear aromatic resin obtained in the above step S52, heat it to 1600°C at a rate of 3°C / min under an argon atmosphere and keep it warm for 2 hours to calcine it to obtain a high-performance carbon material that can be used as an electrode material for a sodium ion battery. The carbon material is cooled and dried for later use.

[0089] Example 5

[0090] The preparation method of the carbon material provided in Example 5 is basically the same as the preparation method of the carbon material provided in Example 1. The difference between the two is that: - While keeping the total amount unchanged, the sodium hydroxide solution was replaced by an ammonia solution.

[0091] Example 6

[0092] The preparation method of the carbon material provided in Example 6 is basically the same as the preparation method of the carbon material provided in Example 2, and the only difference between the two is that the time of the cross-linking condensation reaction is changed from 5 hours to 12 hours.

[0093] Example 7

[0094] The preparation method of the carbon material provided in Example 7 is basically the same as the preparation method of the carbon material provided in Example 4, and the only difference between the two is that the calcination temperature is changed from 1600°C to 800°C.

[0095] Comparative Example 1

[0096] The preparation method of the carbon material provided in Comparative Example 1 is substantially the same as the preparation method of the carbon material provided in Example 1, and the difference between the two is that the polyhydroxyphenol cross-linking agent in step S22 is replaced by terephthalic acid.

[0097] Comparative Example 2

[0098] The preparation method of the carbon material provided in Comparative Example 2 is basically the same as the preparation method of the carbon material provided in Example 1, and the only difference between the two is that the method of weighing 10g of catalytic diesel, 4.44g of hydrolyzed tannic acid and 4.81g of the polyhydroxyphenol cross-linking agent obtained in the above step S21 in step S22 is changed to only weighing 10g of catalytic diesel and 4.81g of the polyhydroxyphenol cross-linking agent obtained in the above step S21, that is, no biomass is used in Comparative Example 2.

[0099] Specifically, by conducting electrochemical performance tests on the carbon materials obtained in the above-mentioned Example 1, Example 2, Example 3, Example 4, Example 5, Example 6, Example 7, Comparative Example 1 and Comparative Example 2, the electrochemical performance test results of each carbon material are shown in Table 1 below.

[0100] Among them, the process of testing the electrochemical properties of the carbon material may include: mixing the carbon material, the conductive agent and the binder in a mass ratio of 8:1:1, adding N-methylpyrrolidone (NMP) as a solvent, stirring evenly and then coating it evenly on the aluminum foil, drying it in a vacuum oven for 12 hours to obtain the carbon-coated aluminum foil, and cutting the obtained carbon-coated aluminum foil into pole pieces of the required diameter, and then using the obtained pole pieces as electrodes, Whatman glass fiber as diaphragms, and 1 mol / L NaPF6 solution as electrolytes to assemble the battery, and for the assembled battery, testing the reversible capacity and platform capacity at different current densities in the test voltage range of 0.01 to 2.0 V, and obtaining the test results as shown in Table 1 below.

[0101] Table 1

[0102]

[0103] It can be seen from the test results in Table 1 that when the carbon materials prepared in Examples 1 to 7 are used as sodium ion battery electrode materials, the overall electrochemical performance of the sodium ion battery can be effectively improved. For example, the reversible capacity of the sodium ion battery at different current densities can be greatly improved.

[0104] By comparing Example 1 with Comparative Example 1, it can be seen that the polyhydroxyphenol cross-linking agent is more conducive to the formation of a carbon material with high electrochemical performance in the subsequent process of carbonizing the obtained condensed polycyclic polynuclear aromatic resin to obtain the carbon material than the traditional cross-linking agent.

[0105] By comparing Example 1 with Comparative Example 2, it can be seen that the introduction of biomass is conducive to the formation of a carbon material with high electrochemical performance in the subsequent process of carbonizing the obtained condensed polycyclic polynuclear aromatic resin to obtain the carbon material.

[0106] As can be seen from the above, the preparation method of the carbon material provided in this embodiment is to obtain a polyhydroxyphenol cross-linking agent by mixing polyformaldehyde, phenolic substances and alkaline solution, and then adding the polyhydroxyphenol cross-linking agent to carry out a cross-linking condensation reaction after mixing the rich aromatic oil with biomass to obtain a condensed polycyclic polynuclear aromatic resin, and then carbonizing the condensed polycyclic polynuclear aromatic resin to obtain a carbon material, thereby providing a method for preparing a high-performance carbon material that can be used as an electrode material for a sodium ion battery using petrochemical rich aromatic oil and biomass as raw materials, and the method is rich in polar functional groups. The biomass is introduced into the petrochemical rich aromatic oil, and the petrochemical rich aromatic oil and the biomass rich in polar functional groups are interconnected through a polyhydroxyphenol cross-linking agent, so that polar functional groups (for example, oxygen-containing functional groups) can be introduced into the obtained condensed polycyclic polynuclear aromatic resin to regulate the structural properties of the final condensed polycyclic polynuclear aromatic resin-based carbon material, thereby greatly improving the metal ion storage capacity of the final condensed polycyclic polynuclear aromatic resin-based carbon material, making it conducive to the storage of alkali metal ions with large ion radius, and can be well applied in metal ion batteries.

[0107] In order to better implement the method for preparing the carbon material provided in the embodiments of the present application, the embodiments of the present application further provide a carbon material, which is prepared by the method for preparing the carbon material provided in any of the above embodiments.

[0108] Specifically, the carbon material has good electrode activity and can be used as an electrode material for sodium ion batteries.

[0109] Furthermore, it should be noted that the carbon material in the embodiments of the present application is prepared by the method for preparing the carbon material provided in any of the above embodiments, and therefore has all the same beneficial effects, which will not be described in detail in this embodiment.

[0110] Based on the carbon material described in the above embodiments, this embodiment will further describe the carbon material from the perspective of the application method.

[0111] The application method of the carbon material provided in the embodiment of the present application can be applied to the scene of making battery electrodes. The specific process of the application method of the carbon material can be as follows:

[0112] Use carbon materials to make metal ion battery negative electrodes.

[0113] Specifically, the carbon material provided in any of the above embodiments of the present application can be used to make a negative electrode of a metal ion battery, wherein the metal ion battery can be specifically a sodium ion battery, a lithium ion battery or a potassium ion battery.

[0114] Furthermore, in a specific implementation, the carbon material provided in any of the above embodiments can be mixed with a conductive agent and a binder and a solvent can be added to obtain a slurry, and then the slurry can be coated on a substrate and dried to obtain an electrode plate. Among them, the conductive agent can be specifically a super p conductive agent (i.e., small particle conductive carbon black). The binder can be specifically PVDF (i.e., polyvinylidene fluoride). The solvent can be specifically NMP (i.e., N-methylpyrrolidone). The substrate can be specifically copper foil or aluminum foil.

[0115] Exemplarily, the carbon material, conductive agent and binder provided in any of the above embodiments can be mixed in a mass ratio of 8:1:1 and a solvent can be added to obtain a slurry, and then the slurry can be evenly coated on a substrate and placed in a vacuum oven to dry for 12 hours to obtain a carbon-coated substrate. The carbon-coated substrate is then cut into pole pieces of the required diameter to obtain a metal ion battery negative electrode.

[0116] In the embodiments of the present application, by using the carbon material provided in any of the above embodiments to prepare the negative electrode of the metal ion battery, the storage capacity of the negative electrode of the metal ion battery for metal ions (especially alkali metal ions with a large ionic radius) can be effectively improved, thereby improving the electrochemical performance of the metal ion battery.

[0117] In the above embodiments, the description of each embodiment has its own emphasis. For parts that are not described in detail in a certain embodiment, reference can be made to the relevant descriptions of other embodiments.

[0118] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.

Claims

1. A method for preparing a carbon material, characterized in that: include: The polyformaldehyde, phenolic substances and alkaline solution are mixed and reacted to obtain a polyhydroxyphenol cross-linking agent; The aromatics-rich oil is mixed with biomass, and then the polyhydroxyphenol cross-linking agent is added to carry out a cross-linking condensation reaction to obtain a condensed polycyclic polynuclear aromatic resin; The condensed polycyclic polynuclear aromatic resin is carbonized to obtain a carbon material.

2. The preparation method according to claim 1, characterized in that: The method comprises mixing paraformaldehyde, phenolic substances and alkaline solution and reacting them to obtain a polyhydroxyphenol crosslinking agent, which comprises: dissolving paraformaldehyde and phenolic substances in an alkaline solution to form a mixed solution; The mixed solution is stirred and reacted at a first predetermined temperature for a first predetermined time, and then allowed to stand and separate for a second predetermined time to obtain a polyhydroxyphenol cross-linking agent, wherein the first predetermined temperature is 20 to 90° C., the first predetermined time is 3 to 48 hours, and the second predetermined time is 6 to 24 hours.

3. The preparation method according to claim 1, characterized in that: The phenolic substances include one or more of phenol, catechol, hydroquinone, resorcinol, phloroglucinol, p-tert-butylphenol, p-tert-octylphenol, and p-methylphenol; the alkaline solution is an aqueous solution of any one or more combinations of sodium hydroxide, potassium hydroxide, and ammonia water, and the mass concentration of the alkaline solution is 2% to 50%; the mass ratio of the polyformaldehyde to the phenolic substances is (30 to 55): (45 to 70); the mass ratio of the polyformaldehyde to the alkali in the alkaline solution is (1 to 2.5): (0.5 to 1.5).

4. The preparation method according to claim 1, characterized in that: The aromatics-rich oil includes one or more of catalytic diesel, ethylene tar, ethylene tar residue and ethylene tar light fraction; the biomass includes one or more of hydrolyzed tannic acid, condensed tannic acid, cellulose, starch and lignin.

5. The preparation method according to claim 1, characterized in that: The mass ratio of the aromatic-rich oil, the biomass and the polyhydroxyphenol cross-linking agent is (45-55): (5-20): (25-50).

6. The preparation method according to claim 1, characterized in that: The aromatics-rich oil is mixed with biomass and then the polyhydroxyphenol cross-linking agent is added to carry out a cross-linking condensation reaction to obtain a condensed polycyclic polynuclear aromatic resin, comprising: After the aromatic-rich oil and biomass are mixed, the polyhydroxyphenol cross-linking agent is added, and the reaction is stirred at a second predetermined temperature for a third predetermined time to obtain a condensed polycyclic polynuclear aromatic resin, wherein the second predetermined temperature is 120-260° C., and the third predetermined time is 2-10 hours.

7. The preparation method according to claim 1, characterized in that: The step of carbonizing the condensed polycyclic polynuclear aromatic resin to obtain a carbon material comprises: The condensed polycyclic polynuclear aromatic resin is calcined to obtain a carbon material.

8. The preparation method according to claim 7, characterized in that: The heating rate of the calcination is 1-5°C / min; the terminal temperature of the calcination is 800-1600°C; the heat preservation time of the calcination is 1-10h; and the calcination is carried out under a protective gas atmosphere.

9. A carbon material, characterized in that The method is prepared by the method according to any one of claims 1 to 8.

10. A method for applying a carbon material, characterized in that: include: The carbon material according to claim 9 is used to prepare the negative electrode of the metal ion battery.

Citation Information

Patent Citations

  • Lignin-phenolic resin-based hard carbon material as well as preparation method and application thereof

    CN117326546A

  • Hard carbon precursor, hard carbon and preparation method thereof, and sodium battery

    CN117466277A

  • Preparation method of COPNA resin-based carbon sodium ion battery negative electrode material

    CN117466279A

  • Method for controllably preparing phenolic resin-based hard carbon material and application of phenolic resin-based hard carbon material

    CN118083950A

  • Preparation method of high-yield biomass-based sodium ion battery hard carbon negative electrode material

    CN118343735A

Cited By

  • Polyhydroxy phenol cross-linking agent and preparation method and application method thereof

    CN119954611A

  • Polyhydroxy phenolic crosslinking agents, methods of making and using the same

    CN119954611B